2017
DOI: 10.15244/pjoes/64747
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electromagnetic Fields on Prooxidant/Antioxidant Balance in Rat Liver

Abstract: The potential health consequences of common exposure of human organisms to high-voltage industrial frequency and radio-frequency electromagnetic fields have not yet been completely recognized. The aim of this study was to evaluate the impact of a 50 Hz electromagnetic field generated by high-voltage alternating electric current transmission lines, a 900 MHz electromagnetic field emitted by mobile phones, and simultaneous exposure to those forms of electromagnetic fields on prooxidant and antioxidant processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Our results from different analysis tests confirm each other and are consistent with the findings of many previous studies [Akdag et al, 2016; Sieroń‐Stołtny et al, 2017; Alkis et al, 2019a; Yang et al, 2020], suggesting that exposure to MWR can trigger DNA damage and oxidative stress. A number of experimental and epidemiological studies have revealed that excessive production of ROS occurs during high levels of MWR exposure and it causes health risks [Tomruk et al, 2009; Ozorak et al, 2013; Cetin et al, 2014; Alkis et al, 2019a,b].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results from different analysis tests confirm each other and are consistent with the findings of many previous studies [Akdag et al, 2016; Sieroń‐Stołtny et al, 2017; Alkis et al, 2019a; Yang et al, 2020], suggesting that exposure to MWR can trigger DNA damage and oxidative stress. A number of experimental and epidemiological studies have revealed that excessive production of ROS occurs during high levels of MWR exposure and it causes health risks [Tomruk et al, 2009; Ozorak et al, 2013; Cetin et al, 2014; Alkis et al, 2019a,b].…”
Section: Discussionsupporting
confidence: 92%
“…A number of experimental and epidemiological studies have revealed that excessive production of ROS occurs during high levels of MWR exposure and it causes health risks [Tomruk et al, 2009; Ozorak et al, 2013; Cetin et al, 2014; Alkis et al, 2019a,b]. Sieroń‐Stołtny et al [2017] reported that exposure to the radiofrequency EMF that is radiated by cell phones causes an intense pro‐oxidant process and decreases antioxidant enzyme activity in the liver tissue of rats. Celik et al [2016] stated that following the exposure of EMR at 2.45 GHz, the lipid peroxidation levels were raised in the liver and brain of rats, and that activity of glutathione peroxidase (GSH‐Px), β‐carotene, vitamin‐E, and vitamin‐A levels were reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation